2019
DOI: 10.11628/ksppe.2019.22.2.199
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Viewing Natural Scenery Indoors on Middle School Students’ Changes in Mood States and Concentration

Abstract: The purpose of this study was to investigate the mood states and concentration of students when they see the natural scenery indoors throughout the Free Semester Program (FSP) of middle school. The subjects were total 180 students comprised of 60 students in the group viewing natural scenery, 60 students in the group viewing urban scenery and 60 students in the control group from the first year of middle school located in Daejeon, and the experiment was carried out from September 3 to October 30, in 2018. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The findings that the image‐only condition elicited a positive change in mood and well‐being is consistent with previous research that showed positive effects of viewing nature scenery on our psychological (Shin & Shin, 2019) and physiological health (Jo et al, 2019). These results also echo previous studies using Project Soothe images as a tool to decrease negative affect and depressive moods (Guerrero, 2017; Wong, 2019; Yang, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings that the image‐only condition elicited a positive change in mood and well‐being is consistent with previous research that showed positive effects of viewing nature scenery on our psychological (Shin & Shin, 2019) and physiological health (Jo et al, 2019). These results also echo previous studies using Project Soothe images as a tool to decrease negative affect and depressive moods (Guerrero, 2017; Wong, 2019; Yang, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Among all, images depicting nature scenes appear to elicit mood benefits. Findings have shown that when students viewed natural scenery compared to viewing urban scenery or not viewing scenery at all, their tension, depression, anger, fatigue and confusion decreased, while vigour, calmness and concentration increased (Shin & Shin, 2019). Indeed, the psychological benefits of being in nature have been thoroughly researched (Bowler et al, 2010), with findings indicating that even brief nature contact can reliably improve hedonic and self‐transcendent emotions (Neill et al, 2018).…”
Section: Introductionmentioning
confidence: 99%